Technological and organizational factors influencing the internet banking use among SMES in Yemen: the mediating role of attitude - Nabil, Al-Fahim; Abdulghafor, Rawad Abdulkhaleq Abdulmolla (Springer Nature Singapore Pte Ltd., 2021)
This study proposes the TOE framework that incorporates the technological and organizational factors to address the utilization of the united model within the use of IB as well as to examine the influence of the attitude mediator on the relationship between the use of IB and SMEs in developing countries particularly the Republic of Yemen. The model includes six exogenous variables, one mediator, and an endogenous variable. The exogenous variables contain technological factors (ease of use, trust, system quality) and organizational factors (bank support, organization readiness, ICT readiness) as well as attitude to use IB as a mediator and the endogenous variables comprise of actual usage of IB. Besides, this study aims at identifying the mediating role of attitude variables and their impact on the use of IB among SMEs in Yemen. The sample of this study comprises 280 SMEs and the analysis were carried out using Structural Equation Modelling (Amos) to examine the causal relationships among the study latent variables. The results indicate that bank support, ICT readiness, ease of use, and system quality have significant and positive effects on the attitude to use IB however ICT readiness did not have a significant effect. In addition, organization readiness, system quality, and attitude have a significant impact on actual usage of IB among SMEs in Yemen, meanwhile, ease of use and trust did not have a significant impact on the actual usage of IB among SMEs in Yemen. Furthermore, the results indicate that the attitude has a full mediation impact on the relationship between organization readiness, ease of use, trust, and actual use of IB, a partial mediation impact on the relationship between bank support, system quality, and IB use, and no mediation impact on the relationship between bank ICT readiness and actual usage of IB among SMEs in Yemen. Finally, the findings of this study provide the Yemeni SMEs with a comprehensive set of products and services to operate efficiently by automating several critical banking services and activities which enables customers to engage with their banks electronically